2017
DOI: 10.1038/srep40726
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Accumulates in Neurogenic Brain Regions as Revealed by High Resolution Ion Imaging

Abstract: Lithium (Li) is a potent mood stabilizer and displays neuroprotective and neurogenic properties. Despite extensive investigations, the mechanisms of action have not been fully elucidated, especially in the juvenile, developing brain. Here we characterized lithium distribution in the juvenile mouse brain during 28 days of continuous treatment that result in clinically relevant serum concentrations. By using Time-of-Flight Secondary Ion Mass Spectrometry- (ToF-SIMS) based imaging we were able to delineate tempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 55 publications
2
29
0
Order By: Relevance
“…The intra- and extracellular lithium concentrations required to obtain the observed effects in the brain are not known, but we recently showed that serum concentrations of 1.2 mM in mice yielded brain tissue concentrations in the range of 0.82 - 0.05 mM, where the highest concentrations were observed in the neurogenic regions [34]. Lithium did not appear to protect medulloblastoma cells from radiation-induced cell death in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…The intra- and extracellular lithium concentrations required to obtain the observed effects in the brain are not known, but we recently showed that serum concentrations of 1.2 mM in mice yielded brain tissue concentrations in the range of 0.82 - 0.05 mM, where the highest concentrations were observed in the neurogenic regions [34]. Lithium did not appear to protect medulloblastoma cells from radiation-induced cell death in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…was sufficient to yield a lithium serum concentration of 0.7-0.9 mM in mice (Zanni et al 2017), which is equivalent to the commonly used 0.6-1.2 mM therapeutic range in humans.…”
Section: Lithium In Vivo Administrationmentioning
confidence: 88%
“…Female littermates (5-6 animals in each cage) were randomly assigned to lithium chow ( Netherlands). This regimen was determined in our previous study (Zanni et al 2017) and…”
Section: Lithium In Vivo Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…For years lithium (Li + ) is known as a potent mood stabilizer. Actual experiments show in this connection that the ion accumulates in neurogenic brain regions [122]. However, in earlier culture experiments it was demonstrated that Li + ions can also elicit the early stages of epithelial differentiation in isolated nephrogenic mesenchyme [123].…”
Section: Drugs For Prolongation Of Nephrogenesismentioning
confidence: 98%